Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173841
|View full text |Cite
|
Sign up to set email alerts
|

StammerApp

Abstract: Stammering is a speech disorder affecting approximately 1% of the worldwide population. It can have associated impacts on daily life, such as loss of confidence in social situations and increased anxiety levels (particularly when speaking to strangers). Work exploring the development of digital tools to support people who stammer (PwS) is emerging. However, there is a paucity of research engaging PwS in the design process, with participation being facilitated mainly in testing phases. In this paper, we describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The tool uses active learning to identify words that the user is likely to encounter issues with, and suggests alternative words that may be easier to speak; no user study has been reported. Finally, McNaney et al [49] employed a multi-stakeholder co-design process to design StammerApp, a mobile app that allows users to set goals, practice, and reflect on their experiences in especially challenging situations. While the project did not focus on speech input, it provides a qualitative understanding of a total of 39 participants' experiences with stammering, including specific challenges (e.g., talking on the phone), and a general desire to be able to "stammer openly and feel more confident and relaxed with their own voice. "…”
Section: Accessibility Of Speech Recognition Systemsmentioning
confidence: 99%
“…The tool uses active learning to identify words that the user is likely to encounter issues with, and suggests alternative words that may be easier to speak; no user study has been reported. Finally, McNaney et al [49] employed a multi-stakeholder co-design process to design StammerApp, a mobile app that allows users to set goals, practice, and reflect on their experiences in especially challenging situations. While the project did not focus on speech input, it provides a qualitative understanding of a total of 39 participants' experiences with stammering, including specific challenges (e.g., talking on the phone), and a general desire to be able to "stammer openly and feel more confident and relaxed with their own voice. "…”
Section: Accessibility Of Speech Recognition Systemsmentioning
confidence: 99%